Complex Networks in Software, Knowledge, and Social Systems - Savić, Miloš; Ivanović, Mirjana; Jain, Lakhmi C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides a comprehensive review of complex networks from three different domains, presents novel methods for analyzing them, and highlights applications with accompanying case studies. Special emphasis is placed on three specific kinds of complex networks of high technological and scientific importance: software networks extracted from the source code of computer programs, ontology networks describing semantic web ontologies, and co-authorship networks reflecting collaboration in science. The book is primarily intended for researchers, teachers and students interested in complex networks and network data analysis. However, it will also be valuable for researchers dealing with software engineering, ontology engineering and scientometrics, as it demonstrates how complex network analysis can be used to address important research issues in these three disciplines.
Introduction to Complex Networks -- Fundamentals of Complex Network Analysis -- Analysis of Software Networks -- Analysis of Ontology Networks -- Co-authorship Networks: An Introduction -- Extraction of Co-authorship Networks -- Analysis of Co-authorship Networks. .
Keywords: Computational intelligence; Dynamics; Nonlinear theories; Artificial intelligence; Graph theory; Library science; Computational Intelligence; Applied Dynamical Systems; Artificial Intelligence; Graph Theory; Library Science